Faith-Based Policing and Human Rights: A Socio-Legal Analysis of Hisbah Operations in Kano State - Nuhu Mukhtar Nuhu; Kawu Adamu Sule (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
This study critically examines the Hisbah Corps in Kano State, Nigeria, as an instance of faith-based policing operating within a plural legal framework. The Hisbah, tasked with enforcing Islamic moral codes under Shari’ah, functions alongside Nigeria’s secular Constitution, creating tensions between religious authority and constitutional rights. Employing a qualitative socio-legal design, the research combines doctrinal legal analysis of constitutional, Shari’ah, and human rights texts with empirical fieldwork through semi-structured interviews with Hisbah officials, legal practitioners, community stakeholders, and human rights advocates. Findings reveal three key themes: legal ambiguities in the Hisbah mandate, human rights implications affecting women and low-income populations, and varied public perceptions of legitimacy and fairness. The results indicate that while segments of the Muslim community support Hisbah’s moral role, its operations often exceed formal authority, disproportionately affect vulnerable groups, and undermine due process. The study concludes that aligning faith-based policing with democratic norms requires clear legal frameworks, independent oversight, and human rights-focused training. These insights contribute to discussions on legal pluralism, religious authority, and inclusive governance in plural societies, linking local challenges to Sustainable Development Goal 16 on peace, justice, and strong institutions.